1997
DOI: 10.1246/cl.1997.617
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Aryl Mesylates Catalyzed by Nickel Complexes

Abstract: Aryl mesylates were found to be deoxygenatively reduced into the corresponding aromatic hydrocarbons by using nickel(0)-dppb/PPh3 catalyst with zinc powder and an alcohol as a hydrogen donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Further optimization of the reaction conditions provided access aryl mesylates as available substrates 403. While dppp in methanol was effective for reduction of tosylates, dppb showed better reactivity for mesylates in methanol/DMF (30%) mixture.…”
Section: Nickel-catalyzed Reactions Of Aryl and Vinyl Sulfonates Amentioning
confidence: 99%
“…Further optimization of the reaction conditions provided access aryl mesylates as available substrates 403. While dppp in methanol was effective for reduction of tosylates, dppb showed better reactivity for mesylates in methanol/DMF (30%) mixture.…”
Section: Nickel-catalyzed Reactions Of Aryl and Vinyl Sulfonates Amentioning
confidence: 99%
“…For example, in 1991, Sasaki’s group documented a very early example of reduction of aryl triflates catalyzed by NiBr 2 (PPh 3 ) 2 /dppp with Zn dust as the reductant in methanol . Six years later, in 1997, the same group achieved the reduction of aryl mesylates via changing the dppp ligand to dppb . In 1992, Tada’s group reported a nice example of reduction of aryl tosylates via a NiCl 2 –NaBH 4 catalytic system; however, NiCl 2 was utilized in a stoichiometric amount .…”
Section: Phenol C–o Functionalizationsmentioning
confidence: 98%
“…122 Six years later, in 1997, the same group achieved the reduction of aryl mesylates via changing the dppp ligand to dppb. 123 In 1992, Tada's group reported a nice example of reduction of aryl tosylates via a NiCl 2 −NaBH 4 catalytic system; however, NiCl 2 was utilized in a stoichiometric amount. 124 Later, in 1994, Tı ́maŕ's group employed Raney Ni as the catalyst with H 2 as the reductant to realize the reduction of aryl tosylates and mesylates.…”
Section: C−h Bond Formation (Hydrogenolysis Of C−o)mentioning
confidence: 99%
“…[23] Later, the use of Raney nickel as a catalyst for the transfer hydrogenation of aryl and vinyl perfluoroalkyl sulfonates was compared with palladium and PtO 2 catalysts, and a very high potential for deoxygenation by using this catalyst was found. Sasaki et al showed the deoxygenation of aryl triflates [25] and mesylates [26] with NiBr 2 (PPh 3 ) 3 /dppp as the catalyst, zinc as the reductant, and methanol as the hydrogen donor. Sasaki et al showed the deoxygenation of aryl triflates [25] and mesylates [26] with NiBr 2 (PPh 3 ) 3 /dppp as the catalyst, zinc as the reductant, and methanol as the hydrogen donor.…”
Section: Nickel-catalyzed Deoxygenationsmentioning
confidence: 99%